Increment of antimycobaterial activity on lichexanthone derivatives - Micheletti, Ana Camila; Honda, Neli Kika; Pavan, Fernando R. [UNESP]; Leite, Clarice Q.F. [UNESP]; De Fatima Cepa Matos, Maria; Perdomo, Renata Trentin; Bogo, Danielle; Alcantara, Glaucia Braz; Beatriz, Adilson (Bentham Science Publishers, 2013)
A new dihydropyranexanthone derived from the natural xanthone lichexanthone (1) was synthesised and, together with other 18 derivatives including ω-bromo and ω-aminoalkoxylxanthones (containing methyl, ethyl, propyl, tertbutylamino and piperidinyl moieties), were tested against Mycobacterium tuberculosis. Nine ω-aminoalkoxylxanthones showed good antimycobacterial activity, and their in vitro cytotoxicity was determined using VERO cells in order to calculate the selectivity index (SI). One of these nitrogenated xanthone derivatives showed very promising results, with MIC of 2.6 μM and SI of 48. This MIC is comparable to values found in first and second line drugs commonly used to treat TB. In order to understand better about this compound, it was evaluated together with two other ones that showed good SI, against resistant clinical strains of M. tuberculosis to verify the existence of cross-resistance. A chemometrical approach was useful to establish a pattern of antitubercular activity among the group of ω- aminoalkoxylxanthones, according to some structural and chemical features. © 2013 Bentham Science Publishers.
Keywords: Chemometrics; Lichen; Structural modifications; Tuberculosis; Xanthone